Assessment of Placebo Response in Objective and Subjective Outcome Measures in Rheumatoid Arthritis Clinical Trials - Vollert, Jan (JAMA Netw Open, 2020)
IMPORTANCE: Large placebo responses in randomized clinical trials may keep effective medication from reaching the market. Primary outcome measures of clinical trials have shifted from patient-reported to objective outcomes, partly because response to randomized placebo treatment is thought to be greater in subjective compared with objective outcomes. However, a direct comparison of placebo response in subjective and objective outcomes in the same patient population is missing. OBJECTIVE: To assess whether subjective patient-reported (pain severity) and objective inflammation (C-reactive protein [CRP] level and erythrocyte sedimentation rate [ESR]) outcomes differ in placebo response. DESIGN, SETTING, AND PARTICIPANTS: The placebo arms of 5 double-blind, randomized, placebo-controlled clinical trials were included in this cross-sectional study. These trials were conducted internationally for 24 weeks or longer between 2005 and 2009. All patients with rheumatoid arthritis randomized to placebo (N = 788) were included. Analysis of data from these trials was conducted from March 27 to December 31, 2019. INTERVENTION: Placebo injection. MAIN OUTCOMES AND MEASURES: The difference (with 95% CIs) from baseline at week 12 and week 24 on a 0- to 100-mm visual analog scale to evaluate the severity of pain, CRP level, and ESR. RESULTS: Of the 788 patients included in the analysis, 644 were women (82%); mean (SD) age was 51 (13) years. There was a statistically significant decrease in patient-reported pain intensity (week 12: −14 mm; 95% CI, −12 to −16 mm and week 24: −20 mm; 95% CI, −16 to −22 mm). Similarly, significant decreases were noted in the CRP level (week 12: −0.51 mg/dL; 95% CI, −0.47 to −0.56 mg/dL and week 24: −1.16 mg/dL; 95% CI, −1.03 to −1.30 mg/dL) and ESR (week 12: −11 mm/h; 95% CI, −10 to 12 mm/h and week 24: −25 mm/h; 95% CI, −12 to −26 mm/h) (all P < .001). CONCLUSIONS AND RELEVANCE: The findings of this study suggest that improvements in clinical outcomes among participants randomized to placebo were not limited to subjective outcomes. Even if these findings could largely demonstrate a regression to the mean, they should be considered for future trial design, as unexpected favorable placebo responses may result in a well-designed trial becoming underpowered to detect the treatment difference needed in clinical drug development.